Phenolic and flavonoid content of Elaeagnus angustifolia L. (leaf and flower) - Fereshte Saboonchian; Rashid Jamei; Siavash Hosseini Sarghein (Avicenna Journal of Phytomedicine, 2014)
Objectives: Leaves and flowers ofElaeagnus angustifolia contain phenolic and flavonoid compounds. These compounds have antioxidant properties that protect cells from oxidative damage. The aim of this study was to determine and analyze total phenolic and flavonoid content of leaves and flowers in two E. angustifolia variants using different solvents (ethanol and methanol). Materials and Methods: Ethanolic and methanolic extracts of the plant leaves and flowers were prepared. Experiments were carried out to measure their phenolic and flavonoid content using two solvents. Data were analyzed using Instat-N software. Results:Results showed that the amount of phenolic and flavonoid compounds in both ethanolic and methanolic extracts was higher in Fariman variant compared with Mashhad variant. Ethanolic and methanolic extracts of Fariman variant had the highest amount of phenolic compound (10.91±0.18, 10.28± 0.36 mgGAE/100gFW, respectively) and also the highest amounts of flavonoids (5.80±0.10, 3.36±0.05 mgQE/100gFW, respectively). Phenolic and flavonoids compounds were better extracted using methanol and ethanol solvent. Conclusion: In both varieties and solvents, the amount of phenolic and flavonoids compounds in leaves were higher than flowers. In addition, the phenolic and flavonoids compounds were higher in Fariman compared to Mashhad variants.